New Zealanders working non-standard hours also have greater exposure to other workplace hazards. (21st April 2017) - Jay, Sarah M.; Gander, Philippa H.; Eng, Amanda; Cheng, Soo; Douwes, Jeroen; Ellison-Loschmann, Lis; McLean, Dave; Pearce, Neil; 'tMannetje, Andrea
ABSTRACT: Exposure to workplace hazards, such as dust, solvents, and fumes, has the potential to adversely affect the health of people. However, the effects of workplace hazards on health may differ when exposure occurs at different times in the circadian cycle, and among people who work longer hours or who do not obtain adequate sleep. The aim of the present study was to document exposures to workplace hazards across a national sample of New Zealanders, comparing people who work a standard 08:00 −17:00 h Monday-to-Friday working week (Std hours) and those who do not (N-Std hours). New Zealanders ( n = 10 000) aged 20–64 yrs were randomly selected from the Electoral Roll to take part in a nationwide survey of workplace exposures. Telephone interviews were conducted between 2004 and 2006, using a six-part questionnaire addressing demographics, detailed information on the current or most recent job (including exposures to a range of workplace hazards), sleep, sleepiness, and health status. N-Std hours were categorised on the basis of: being required to start work prior to 07:00 h or finish work after 21:00 h and/or; having a regular on-call commitment (at least once per week) and/or; working rotating shifts and/or; working night shift(s) in the last month. The response rate was 37% ( n = 3003), with 22.2% of participants ( n = 656) categorised as working N-Std hours. Industry sectors with the highest numbers of participants working N-Std hours were manufacturing, health and community services, and agriculture, fishing, and forestry. Response rate was 37% ( n = 3003) with 22.2% ( n = 656) categorised as working N-Std hours. Participants working N-Std hours were more likely to be exposed to all identified hazards, including multiple hazards (OR = 2.45, 95% CI = 2.01–3.0) compared to those working Std hours. Participants working N-Std hours were also more likely to report 'never/rarely' getting enough sleep (OR = 1.38, 95% CI = 1.15–1.65), 'never/rarely' waking refreshed (OR = 1.23, 95% CI = 1.04–1.47), and excessive sleepiness (OR = 1.77, 95% CI = 1.29–2.42). New Zealanders working N-Std hours are more likely to be exposed to hazards in the workplace, to be exposed to multiple hazards, and to report inadequate sleep and excessive sleepiness than their colleagues working a standard 08:00−17:00 h Monday-to-Friday working week. More research is needed on the effects of exposure to hazardous substances outside the usual waking day, on the effects of exposure to multiple hazards, and on the combination of hazard exposure and sleep restriction as a result of shift work.